ANALISIS KUALITAS TERHADAP BATUGAMPING QUARRY HINGGA TEPUNG KALSIUM KARBONAT HASIL PRODUKSI DI PT. SUGIH ALAMANUGROHO - Monika Asworo; Tri Wahyuningsih; Anton Sudiyanto; Olivia Silvi Hermanto; Meindra Setyawan (Journal of Metallurgical Engineering and Processing Technology, 2022)
Limestone is a rock belonging to the type of sedimentary rock, formed as a result of a natural sedimentation process. Limestone is a type of non-metallic mineral that is used in various sectors, such as in the paint industry, glass industry, plastics, paper industry, liming on agricultural land and is also used in the metal smelting industry. Limestone products produced by PT. Sugih Alamanugroho is in the form of calcium carbonate flour (powder) with sizes of 800 and 1,200 mesh. Before being marketed, calcium flour will go through a series of quality analysis processes to determine moisture content, degree of whiteness and residual weight (+800 mesh). The water content test was analyzed using an infrared moisture determination balance tool, aiming to find out what percentage of the water content contained in limestone and calcium carbonate flour. The degree of whiteness was analyzed using a reflectometer. Residual testing was carried out by weight pf the residue after the drying process was carried out in the oven. Based on the data, the calcium carbonate flour produced has passed the quality test, with a moisture content <0.03%, a whiteness degree >89.6% and a residual weight (+800 mesh) <0.05% in accordance with the quality standards of limestone and calcium flour. carbonates that have been determined by the company. So that the packaging and marketing process can then be carried out.Keywords: Limestone, Calcium Carbonate Flour, Moisture, Whiteness, Residue Weight